A Novel Ultra‐Sensitive Semiconductor SERS Substrate Boosted by the Coupled Resonance Effect. Issue 12 (16th April 2019) - Yang, Lili; Peng, Yusi; Yang, Yong; Liu, Jianjun; Huang, Haoliang; Yu, Bohan; Zhao, Jimin; Lu, Yalin; Huang, Zhengren; Li, Zhiyuan; Lombardi, John R.
Abstract: Recent achievements in semiconductor surface‐enhanced Raman scattering (SERS) substrates have greatly expanded the application of SERS technique in various fields. However, exploring novel ultra‐sensitive semiconductor SERS materials is a high‐priority task. Here, a new semiconductor SERS‐active substrate, Ta2 O5, is developed and an important strategy, the "coupled resonance" effect, is presented, to optimize the SERS performance of semiconductor materials by energy band engineering. The optimized Mo‐doped Ta2 O5 substrate exhibits a remarkable SERS sensitivity with an enhancement factor of 2.2 × 10 7 and a very low detection limit of 9 × 10 −9 m for methyl violet (MV) molecules, demonstrating one of the highest sensitivities among those reported for semiconductor SERS substrates. This remarkable enhancement can be attributed to the synergistic resonance enhancement of three components under 532 nm laser excitation: i) MV molecular resonance, ii) photoinduced charge transfer resonance between MV molecules and Ta2 O5 nanorods, and iii) electromagnetic enhancement around the "gap" and "tip" of anisotropic Ta2 O5 nanorods. Furthermore, it is discovered that the concomitant photoinduced degradation of the probed molecules in the time‐scale of SERS detection is a non‐negligible factor that limits the SERS performance of semiconductors with photocatalytic activity. Abstract : A semiconductor surface‐enhanced Raman scattering (SERS)‐active substrate Ta2 O5 is developed, and an important strategy, the "coupled resonance" effect, is presented to optimize its SERS performance by energy band engineering. Furthermore, the unique photocatalytic degradation of probed molecules in the time‐scale of SERS detection by semiconductors is revealed as another non‐negligible factor that limits the SERS performance of some semiconductors with photocatalytic activity.